Use of microwave ablation in the treatment of patients with multiple primary malignant tumors. Issue 4 (31st May 2017) - Han, Yue; Shao, Na; Xi, Xiaoming; Hao, Xuezhi
Abstract : A 56‐year‐old man was admitted to our hospital in 2007, complaining of an irritating cough. Computed tomography examination demonstrated a mass in the right lung and enlargement of the hilar and mediastinal lymph nodes. Small cell lung cancer was confirmed by pathological examination after fibro‐bronchoscope biopsy. The patient was treated with received sequential chemotherapy and radiotherapy. Preventive radiotherapy of the whole brain was performed after complete remission of the lung disease. Seven years after diagnosis, follow‐up computed tomography revealed masses in both the liver and kidney. Subsequent percutaneous biopsy confirmed hepatocellular carcinoma in the liver and renal clear cell carcinoma in the kidney. The patient received microwave ablation for the treatment of both liver and renal tumors, and is doing well with no recurrence after two years of follow‐up.